Anteseden dari consumer loyalty pada sepatu olahraga - Suherman, Zhalsabila; Ganawati, Ganawati (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2024)
The purpose of this study was to determine what factors influence consumer loyalty, with the variables used namely consumer trust, product quality, brand image and customer satisfaction. this study used a purposive sampling technique with 160 samples with the criteria of consumers who use and buy sports shoes from the Adidas, Nike, Ardiles, Diadora and Reebok brands at least once in the last 1 year. The tool used in this research is the Structural Equation Model (SEM) by the AMOS program. The results of this study indicate that there is a positive influence of Consumer Trust on Consumer Loyalty, there is a positive influence on Product Quality Consumer Loyalty, there is a positive influence of Brand Image on Consumer Loyalty, and there is a positive influence of Customer Satisfaction on Consumer Loyalty.